Managing East Asia's Macroeconomic Volatility - Olaberria, Eduardo; Rigolini, Jamele (2012)
East Asia has experienced a dramatic decrease in output growth volatility over the past 20 years. This is good news, as output growth volatility affects poor households because of coping strategies that have long-term, harmful consequences, and the overall economy through its negative impact on economic growth. This paper investigates the factors behind this long decline in volatility, and derives lessons about ways to mitigate renewed upward pressure in face of the financial crisis. The authors show that if, on the one hand, high trade openness has sustained economic growth in the past several decades, on the other hand, it has made countries more vulnerable to external fluctuations. Although less frequent terms of trade shocks and more stable growth rates of trading partners have helped to reduce volatility in the past, the same external factors are now putting renewed pressure on volatility. The way forward seems therefore to be to counterbalance the external upward pressure on volatility by improving domestic factors. Elements under domestic control that can help countries deal with high volatility include more accountable institutions, better regulated financial markets, and more stable fiscal and monetary policies.